The development of evidence-based guidelines to inform the extrication of casualties trapped in motor vehicles following a collision - Nutbeam, Tim (Division of General Surgery, 2023)
Background Motor vehicle collisions (MVCs) are a common cause of injury and death throughout the world. Following an MVC some patients will remain in their vehicles due to injury, the potential for injury or physical obstruction. Extrication is the process of removing injured or potentially injured patients from vehicles following a motor-vehicle collision. Current extrication practices are based on the principles of 'movement minimisation' with the purpose of minimising the incidence of avoidable secondary spinal injury. Movement minimisation adds time to the process of extrication and may result in an excess morbidity and mortality for patients with time dependent injuries. The current extrication approach has evolved without the application of evidence-based medicine (EBM) principles. The principles of EBM; consideration of the relevant scientific evidence, patient values and preferences and expert clinical judgement are used as a framework for this thesis. Aims and Objectives To develop evidence-based guidance for the extrication of patients trapped in motor vehicles by applying EBM principles to this area of practice. This will be achieved through: - Describing the injury patterns, morbidity and mortality of patients involved in MVCs (trapped and not trapped). - To analyse the movement associated with and the time taken to deliver across a variety of extrication methods. - Determining the perceptions of patients who have undergone vehicle extrication and describe their experiences of extrication. - Developing consensus-based guidelines for extrication.